Electrochemical characterization of carbon nanotubes as electrode in electrochemical double-layer capacitors - Chen, J.H.; Li, W.Z.; Wang, D. Z.; Yang, S. X; Wen, J.G.; Ren, Z. F.
Carbon nanotubes uniformly 50 nm in diameter were directly grown on graphite foil. Cyclic voltammetry (CV)shows that the carbon nanotube/ graphite foil electrode has a high specific capacitance (115.7 F/g at a scan rate of 100 mV/ s)and exhibits typical double-layer behavior. A rectangular-shaped CV curve persists even at a scan rate of 100 mV/ s in 1.0 M H SO aqueous solution, which suggests that the carbon nanotube electrode could be an excellent candidate as the electrode 2 4 in electrochemical double-layer capacitors. In addition, the influence of the potential scan rate, aging, and the electrolyte solution on the specific capacitance of nanotube electrodes was also studied.
Keywords: CARBON NANOTUBES; ELECTRODES; CHEMICAL VAPOR DEPOSITION; SCANNING ELECTRON MICROSCOPY (SEM); SPUTTERING